APONTAMENTOS SOBRE O DIREITO À SAÚDE E UM BREVE ESTUDO DE CASO: A APLICAÇÃO DA DECISÃO DO RE 657.718 DO SUPREMO TRIBUNAL FEDERAL EM UMA DEMANDA POR SAÚDE NA CIDADE DE TAVARES – RS (Revista Direito em Debate, 2019)
This article has the objective of to write considerations about the right to health analysing a concrete case where it would be possible to aply a recente decision of the Supreme Court which stabilished that the state would not to pay expensive treatments of healthy without comproved eficacy recognised by ANVISA. First of all it will study the right to healthy in order to classificate it in a dogmatic category. That categories will be, in a brief way, analized when compared whith the possible reservation. After the categorization and the delimitation of the right to healthy in the brazilian law, it will study the decision RE n. 657718 of the Supreme Court of Brazil, that in order to, finally do considerations about the consequences of the decision. The research used the bibliographic method and datas about the decision of Supreme Court, object in analisis.
Keywords: Social Rights; Right to Healthy; Decision of Supreme Court 657.758